Uji Kualitas Briket Batu Bara Campur Biomassa Cangkang Biji Karet Dan Tepung Kanji Sebagai Perekat - Pribadyo Pribadyo (universitas teuku umar, 2016)
Briquetting is the process of small particles agglomerate or without a binder into a certain shape and size with the properties of certain physical and chemical also aimed to improve the quality and efficiency as fuel and easy to use. This study aimed to test the quality of coal briquettes rubber seed shells mixed biomass and starch as an adhesive. The benefits of this research is as an effort to capitalize upon the waste biomass and coal in West Aceh as fuel. In this study the composition of the mixture for each raw material is 70% coal, 20% rubber seed shells and 10% starch, whereas the mesh size varied 30 and 50 with strong briquettes printing press is equal to 120 kgf/cm2. Toughness testing is done using the drop test, moisture content, ash content and density are calculated using a mathematical equation while the calorific value is calculated by automatical calorimeter. The results of water content to 30 mesh size average is at 0415 % and moisture content to a mesh size of 50 is 00:45%. Calorific value for the size of the mesh 30 is equal 4847.2 kal/g and a calorific value of 50 mesh size is equal to 4797. 2 kal/g. ash content to 30 mesh size was 0.13 % and for the size of the mesh 50 is 0.10%. Briquettes toughness analysis results with the drop test for mesh size 30 is sebesar 0,03% and for the size of the mesh 50 is 0.04%. The results of the average density of the mesh size of 30 is 5.10 g/cm3 dan average density of 50 mesh size is equal to 5.45 g/cm3 and the composition of the mixture of coal 70%, biomasssa shell rubber and adhesive 20% 10% with a pressure of 120 kgf/cm2. Keywords: Coal, shell bean gum, starch , automatical calorimeter , testing